Mandibular Symmetrical Bilateral Canine-Lateral Incisors Transposition: Its Early Diagnosis and Treatment Considerations - Yehoshua Shapira; Tamar Finkelstein; Rana Kadry; Shirley Schonberger; Nir Shpack (Case Reports in Dentistry)
Bilateral mandibular tooth transposition is a relatively rare dental anomaly caused by distal migration of the mandibular lateral incisors and can be detected in the early mixed dentition by radiographic examination. Early diagnosis and interceptive intervention may reduce the risk of possible transposition between the mandibular canine and lateral incisor. This report illustrates the orthodontic management of bilateral mandibular canine-lateral incisor transposition. Correct positioning of the affected teeth was achieved on the left side while teeth on the right side were aligned in their transposed position. It demonstrates the outcome of good alignment of the teeth in the dental arch.